The influence of dual CYP17 expression on adrenal steroidogenesis in the South African Angora Goat - Storbeck, Karl-Heinz (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Biochemistry))--Stellenbosch University, 2008.